The Integrating Millealab Into English Language Teaching: A Conceptual Framework For Inclusive Education - Ranggia Dyas Pitaloka; Erwin Hari Kurniawan; Wildan Isna Asyhar (Universitas Islam Lamongan, 2025)
Recent advances in immersive learning technologies have opened new pathways for innovation in English Language Teaching (ELT). Despite this progress, scholarly discussion on the application of Virtual Reality (VR) for inclusion students within Indonesia’s Merdeka Curriculum remains limited. This study conceptually examines the integration of Millealab, an Indonesian-developed VR platform, into inclusive ELT as a means of supporting Sustainable Development Goal (SDG) 4, which emphasizes equitable and quality education for all. The proposed conceptual framework demonstrates how Millealab supports differentiated instruction, enhances learner engagement, and facilitates the design of Individualized Learning Programs (ILPs) aligned with inclusive education principles. By situating Millealab within interconnected pedagogical and technological dimensions, this study contributes to broader discussions on adaptive, accessible, and equitable VR-based instructional design. While challenges related to teacher preparedness and resource availability persist, the findings suggest that Millealab holds strong potential as a transformative model for inclusive ELT. Future empirical research is recommended to validate the framework and examine its long-term educational impact.